(untitled) (Research, Society and Development, 2022)
Listening to music can trigger unpleasant feelings or bring meaning to our lives, both from the cognitive and psychic perspectives. Thus, music can attribute meanings to our personal experiences and act as a regulator of emotions when living these experiences. Song lyrics can often influence behaviours while helping to work on processes of resilience, autonomy, empowerment, and psychosocial rehabilitation. This study aims to analyse the possibilities of music in the process of resignification of life through the discursive productions of individuals after a suicide attempt. A qualitative study was conducted with eight Brazilian adults assisted in a mental health service, in 2018, through semi-structured interviews. The Symbolic Interactionism theoretical framework was used, and the data were submitted for thematic analysis. Three categories were identified: ‘Spirituality as an empowering agent’; ‘Sense of belonging and identification’, and ‘The importance of music as a sensitizer of reasons for living and an instrument of verbalization of feelings. The study provides important findings that merit further investigation regarding interventions and possibilities related to music as a healing method in the process of resignification of life after a suicide attempt.